El uso de sufijos apreciativos en los hablantes lojanos - Gálvez Cordero, Karen Stefanny (2022)
The objective of this research is to analyze the use of appreciative suffixes in Lojan speakers using social variables. It is a research with a qualitative approach, which relies on descriptive statistics for the analysis of the results. During the data collection process, the sociolinguistic interview was used in order to know the vernacular speech, that is, the natural speech of our informants of three generations. Twenty-two people (12 men and 10 women) from the Loja canton participated in the research process. The results show that people who participated in the study use diminutives more frequently than the rest of the appreciative suffixes. Moreover, the suffix ito is the most used by both genders, although it is evident that women use diminutives more than men. However, the use of diminutives by both genders is different: the data collected show that women use them with affective intentions, while men use them to intensify words. Regarding the augmentations, speakers from Loja city of both genders use the suffixes ón/ona and azo/aza. Finally, the use of derogatory suffixes was not recorded in the collected data; however, is evident that both augmentations and diminutives can perform this function, that is to say, that these suffixes have positive and negative values.